Penyuluhan dan Pendampingan Pengolahan Limbah Peternakan Sapi Potong di Kelompok Tani Ternak Sido Mulyo Dusun Pulosari, Desa Jumoyo, Kecamatan Salam, Kabupaten Magelang - Nanung Agus Fitriyanto; Suharjono Triatmojo; Ambar Pertiwiningrum; Yuny Erwanto; Mohammad Zainal Abidin; Endang Baliarti; Yustina Yuni Suranindyah (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2015)
Society services activity on cattle waste management system have been implemented in Sido Mulyo Livestock Farmers Group at Pulosari, Jumoyo, Salam, Magelang. Animal byproducts that consist of feces and urine of cattle wastewas processed into organic fertilizer compost and liquid fertilizer. Sido Mulyo Livestock Farmer Group has one unit of 20 m3 biodigester to accommodate the feces from approximately 30 cattle owned by the group member. Biogas has been used as a fuel source for family group members located around the cage. Slurry resulted from anaerobic digestion of biodigester disposed to pastures located on the right side of the cage. Ownership system in the groupis every group member hasa responsibility for taking care of their own cattle. The number of livestock owned by each member of the SidoMulyoLivestock Farmers Group ranged between 1 to 4 cattle. Society services methods that have been implemented was in the form of mentoring for a member of the Sido Mulyogroup.The other activities that have been implemented was the training and development of cattle industry, especially the handling of livestock waste in the form of feces, urine, and the feed residue. The activities was continued by the manufacture of compost packaging design, followed by the last series of activities such as monitoring and program development. The enthusiasm of the group members in joining to the extension activities is very good. The timing of the extension are determined in the afternoon after members of the group have finished searching feed for their cattle. The sustainability forwaste processing into organic fertilizer compost and liquid organic fertilizer becomes a major concern, because it is highly dependent on consumer demand.